Pandangan Al-Qur'an Mengenai Isu Gender: Analisis Prinsip Kesetaraan Dan Keadilan - Sustriana (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study analyzes how the Quran positions gender issues, focusing primarily on the concept of equality and justice in the relationship between men and women. This research applies a descriptive-analytical method through a thematic interpretation (maudhu'i) approach, which comprehensively examines the sacred verses that address the dynamics of gender relations. The research findings indicate that the holy book affirms the essential equality of men and women in terms of humanity, spirituality, and moral obligations. The differentiation identified in the texts is not intended to demonstrate the supremacy of one gender, but rather illustrates the distribution of societal roles that are contextual and pragmatic in nature, in accordance with the social situation at the time of revelation. Therefore, interpretation of the texts governing gender relations requires a comprehensive approach, taking into account the historical background, linguistic studies, and the objectives of Islamic law (maqasid al-shari'ah). This comprehensive approach is essential so that the interpretation of gender issues in the holy book does not fall into mere literal interpretation but rather conveys a universal message about the principle of justice and human equality before God.